Associated Gas Utilization via miniGTL - World Bank (Washington, DC, 2015)
The flaring of natural gas produced as part of crude oil production operations is a well-known practice which increasingly becomes a non-acceptable option around the globe. In 2010, the Global Gas Flaring Reduction Partnership (GGFR) at the World Bank reported that nearly 5TCF (trillion standard cubic feet or 135 billion cubic meters) of associated gas (AG) was flared worldwide, equal to 20 percent of US consumption emitting 320MM tons of unnecessary CO2 into the atmosphere. This paper provides a high-level overview of the status of gas conversion technologies that are developed for, or are applicable to, the monetization of associated gas. Gas conversion technology is but one out of about half a dozen options to manage or utilize AG such as gas re-injection, power production, compressed natural gas (CNG), liquefied natural gas (LNG) and pipelines. More than 15 technologies were evaluated analyzing the overall technology approach, the strengths and weaknesses of the technology, commercial readiness and technical risk along with product acceptance issues and high level economic attractiveness. The gas volume application range was from sub 1 MMscfd (million standard cubic feet per day) to a maximum of 25MMscfd with the sweet spot at 15MMscfd. The in depth evaluation was based on both publicly available information from websites, papers and patents and on private files by the reviewer. Personal phone calls with all companies answered any open questions. A standard survey was sent to all companies with questions relating to the building of a plant with a capacity of 15MMscfd. The responses are compared and discussed in detail.